The association between solid fuel use and oral health: the mediating effect of depressive symptom - Hui Jin; Hui Jin; Ai-ping Deng; Ai-ping Deng; Hua Tian; Mao-Sheng Ran; Mao-Sheng Ran (Frontiers in Oral Health)
ObjectivesThis study aimed to investigate the associations between solid fuel use and oral health and the mediating effects of depressive symptom.Methods64,521 Indian adults were included in this study. Binary logistic regression was performed to evaluate the associations of solid fuel use with tooth loss, dental cavity, and periodontal disease. Mediating analysis was used to investigate the effects of depressive symptom on the associations between solid fuel use and oral health.ResultsParticipants who claimed solid fuel use for cooking exhibited an increased risk of periodontal disease (OR: 1.35, 95% CI: 1.29–1.42) after adjusting for potential confounders. There were no significant associations of solid cooking fuel with tooth loss and dental caries. 7.89% of the relationship between solid fuel use and periodontal disease was mediated by depressive symptom.ConclusionsThe use of solid cooking fuel is associated with the increased prevalence of periodontal disease. Depressive symptom mediates the relationship between solid fuel use and periodontal disease. In the management of oral heath, the adverse impact of solid fuel use should be considered. Future studies should further clarify the mechanisms underlying the association between solid fuel and periodontal disease.